Genotoxicity assessment of potentially mutagenic nucleoside analogues using ToxTracker®. (1st June 2022) - Brandsma, Inger; Derr, Remco; Zhang, Gaonan; Moelijker, Nynke; Hendriks, Giel; Østerlund, Torben
Abstract: Nucleoside analogues have long been designed and tested in cancer treatment and against viral infections. However, several early compounds were shown to have mutagenic properties as a consequence of their mode-of-action. This limited their use, and several have been discontinued for lengthy treatments or altogether. Nonetheless, nucleoside analogues remain an attractive modality for virally driven diseases, of which many still are without proper treatment options. To quantitatively assess the genotoxic mode-of-action of a panel of nucleoside analogues, we applied the ToxTracker® reporter assay. Many of the early nucleoside analogues showed a genotoxic response. The more recently developed nucleoside analogues, Remdesivir and Molnupiravir that are currently being repurposed for Covid-19 treatment, had a different profile in ToxTracker and did not induce the genotoxicity reporters. Our analyses support the metabolite GS-441524 over the parent analogue Remdesivir. In contrast, Molnupiravir was devoid of clear cellular toxicity while its active metabolite (EIDD-1931) was cytotoxic and induced several biomarkers. Nucleoside analogues continue to be attractive treatment options upon viral infections. ToxTracker readily distinguished between the genotoxic analogues and those with different profiles and provides a basis for clustering and potency ranking, offering a comprehensive tool to assess the toxicity of nucleoside analogues. Highlights: Nucleoside analogues can be mutagenic and carcinogenic because of their MoA. We tested well-known nucleoside analogues using our genotoxicity assay ToxTracker. > 50% of the nucleoside analogues were found to induce genotoxicity in ToxTracker. The data are largely in line with in vivo micronucleus and/or carcinogenicity data. Recently developed nucleoside analogues generally have better toxicity profiles.